Legal Analysis of the Application of Mediation in Civil Cases Between PT. Primadaya Sakti Against Defendants Related to Property Rights and Auction Process (Regulation No. 1259 / Pdt.G / 2024 / PN Dps) - Gayo, Sabela (International Asia Of Law and Money Laundering, 2025)
This article analyzes the decision of the Denpasar District Court related to property rights disputes and the auction process of assets owned by PT. Primadaya Sakti. Through normative juridical approach and Case Studies, a study was conducted on mediation procedures, the enforceability of surety seizures, asset auction processes, and the legal implications of these decisions in the context of property rights protection and Procedural and Substantive justice principles. This study aims to provide a comprehensive overview of the application of criminal and civil procedural law in civil cases involving property assets and auction activities by state institutions.